(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
The aim of this study was to evaluate the prevalence of antibiotic resistance among bacteria isolated from urine cultures of Syrian patients of different genders and age categories. The most frequently identified uropathogen in urine cultures was Escherichia coli (68%). Of the bacterial isolates, 2% were resistant to a single antibiotic, while 98% were resistant to at least two antibiotics. A significantly high in-vitro resistance rate (over 90%) was observed among bacterial isolates, particularly against Cefotaxime, Nalidixic acid, Cefexime, Cephalexin, and Cefpodoxime. Resistance rates for Cefetriaxone, Cefuroxime, and Trimethoprim-Sulfamethoxazole ranged from 70% to 80%. The resistance rates for Nitrofurantoin, Amoxicillin-Clavulanic acid, Ciprofloxacin, and Norfloxacin ranged from 37% to 60%. For some antibiotics, resistance rates remained consistently high across all age groups (Trimethoprim-Sulfamethoxazole, Cephalexin, and Cefexime), while for others, resistance rates increased with increasing patient age (Nitrofurantoin, Ciprofloxacin, and Norfloxacin). Finally, Amikacin, Gentamycin, and Imipenem demonstrated good sensitivity (over 90%) across all age groups.